Numerical treatment of singularly perturbed parabolic partial differential equations with nonlocal boundary condition - Wondimu, Getu Mekonnen; Woldaregay, Mesfin Mekuria; Dinka, Tekle Gemechu; Duressa, Gemechis File (Frontiers in Applied Mathematics and Statistics, 2022)
This paper presents numerical treatments for a class of singularly perturbed parabolic partial differential equations with nonlocal boundary conditions. The problem has strong boundary layers at $x = 0$ and $x = 1$. The nonstandard finite difference method was developed to solve the considered problem in the spatial direction, and the implicit Euler method was proposed to solve the resulting system of IVPs in the temporal direction. The nonlocal boundary condition is approximated by Simpson’s $\frac{1}{3} $ rule. The stability and uniform convergence analysis of the scheme are studied. The developed scheme is second-order uniformly convergent in the spatial direction and first-order in the temporal direction. Two test examples are carried out to validate the applicability of the developed numerical scheme. The obtained numerical results reflect the theoretical estimate.